Ordeal : a thriller - Horst, Jørn Lier, 1970- (Minotaur Books, 2017)
"Together with her one year old daughter Maja, single mother Sofie Lund moves into the house she inherited from her grandfather. Sofie has such painful memories that she has had every trace of the old man removed, every trace but a locked safe that has been bolted to the basement floor. Inside the safe, Sofie finds something shocking that will also become crucial evidence in a case that has plagued Inspector William Wisting for a long time. To follow this lead though, he must cut across important loyalties and undermine confidence in the police force"--